First-line bortezomib benefits patients with multiple myeloma - Dimopoulos, M.A.; Terpos, E. (Nature Reviews Clinical Oncology, 2009)
Bortezomib-based regimens are beneficial in the treatment of patients with symptomatic, newly diagnosed and relapsed or refractory multiple myeloma. researchers who investigated the efficacy and safety of single-agent bortezomib as first-line therapy in patients with myeloma have particularly emphasized the incidence and management of peripheral neuropathy, which is the most common adverse effect of bortezomib administration. © 2009 Macmillan Publishers Limited. All rights reserved.